Judicial valuation of anticipatory proof in Brazilian law - Zufelato, Camilo (2024)
The Brazilian law, through the 2015 Code of Civil Procedure, introduced several changes regarding the early production of evidence. By expanding and flexibilizing the situations in which anticipatory proof is possible, the new legislation eliminates the exclusive precautionary nature of this procedure, thus giving rise to a new autonomous evidentiary action. This fact redefines the concept of evidence in Brazilian law, and this article aims to specifically analyze some aspects of the innovations introduced by the new Code, seeking to draw comparisons with the system of early production of evidence in Peru.